Repository for: Genetic footprints of a rapid and large-scale range expansion: The case of cyclic common vole in Spain ... - Domínguez Villaseñor, Julio César (Dryad, 2023)
Te repository contains the neccesary genetic data (microsatellite allele frequencies and GenBank accesion numbers for cytb haplotypes) to be able to replicate the analyses performed in the manuscript. ... : All the methodological aspects are extensively described in the manuscript. ...